Antecedents of Negative Emotions and Intention to Sabotage: Active and Passive Workplace Mistreatments - Yazdian, Taraneh Foroutan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Workplace mistreatments and aggressions have become pressing issues in today’s multi-generational workplace. Yet, to date, these issues have been widely neglected in the management literature. This study empirically explores the resultant effects of active (i.e., workplace tolerance to incivility) and passive (i.e., workplace ostracism) mistreatment on negative emotion and intention to sabotage by utilizing a generational perspective. Data was collected from bank employees in Nigeria (n=320) and analyzed with the aid of a structural equation modeling. The results revealed that: (1) active and passive workplace mistreatment are relevant factors inflicting negative emotions and intention to sabotage; (2) negative emotion inflicts the intention to sabotage; and (3) negative emotion mediates the relationship between both active and passive workplace mistreatments and intention to sabotage. Furthermore, the impact of passive workplace mistreatment on negative emotion is higher among Gen X and Gen Y cohorts; and its impact on intention to sabotage is higher among baby boomers cohorts. The impact of active workplace mistreatment on negative emotion is higher among Gen Y and baby boomers cohorts; and its impact on intention to sabotage is higher among Gen X and Gen Y cohorts. This study advances our knowledge concerning reactional response of employee from different generation to workplace mistreatments. Based on study’s findings, theoretical and practical implications are identified and discussed. Keywords: Ostracism, Incivility, Negative Emotion, Intention to Sabotage, Generation, Nigeria.

ÖZ: İşyerinde yapılan kötü muamele ve saldırılar bugünün çok nesilli işyerlerinde önemli meselelerden biri haline geldi. Ancak bugüne kadar bu konular yönetim literatüründe yaygın olarak ihmal edilmiştir. Bu çalışma ampirik olarak, nesilden nesnel bir perspektif kullanarak sabotaja yönelik olumsuz duygu ve niyet üzerine aktif (kabalığa karşı işyerinin toleransı) ve pasif (işyerinde dışlama) kötü muamelenin sonuç etkilerini araştırmaktadır. Veriler Nijerya'daki banka çalışanlarından (n = 320) toplandı ve yapısal eşitlik modellemesi yardımıyla analiz edildi. Elde edilen sonuçlar şunları ortaya çıkardı: (1) işyerindeki aktif ve pasif kötü muamele, negatif duygulara ve sabotaja neden olan faktörlerdir; (2) negatif duygu, sabote etme niyetine neden olur ve (3) olumsuz duyguları sabote etmek için hem aktif hem de pasif işyeri kötü muamelesi ve niyeti arasındaki ilişkiye aracılık eder. Dahası, işyerinde yapılan pasif kötü muamelenin olumsuz duygu üzerine etkisi, x-kuşağı ve y-kuşağı’nda daha yüksektir; ve sabotaj niyeti üzerindeki etkisi bebek patlaması kuşakları arasında daha fazladır. Aktif işyeri kötü muamelesinin negatif duygu üzerine etkisi, y-kuşağı ve bebek patlaması kuşakları arasında daha yüksektir; ve sabotaj niyeti üzerindeki etkisi x-kuşağı ve y-kuşağı’nda daha baskınıdır. Bu çalışma, çalışanların farklı nesillerden işyerinde yapılan kötü muamelelere tepkisel tepki ile ilgili bilgilerimizi geliştirmektedir. Çalışmanın bulgularına dayanarak, teorik ve pratik sonuçlar belirlenmiş ve tartışılmıştır. Anahtar Kelimeler: Dışlama, Kabalık, Negatif Duygu, Sabotaj Niyeti, Nesil, Nijerya
Doctor of Philosophy in Business Administration. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2017. Co-Supervisor: Assist. Prof. Dr. A. M. Abubakar and Supervisor: Assoc. Prof. Dr. Tarık Timur.
Keywords: Business Administration; Employees - Abuse of--Quality of work life--Job stress; Work environment--Psychological aspects--Nigeria; Organizational sociology--Social psychology; Work environment--Industrial relations--Dispute resolution; Work Environment--Discrimination in employment; Motivation, morale, discipline; Ostracism; Incivility; Negative Emotion; Intention to Sabotage; Generation; Nigeria